Pengaruh Lokasi dan Pengetahuan terhadap Minat Menabung di Bank Syariah (Studi Mahasiswa IAIN SAS Bangka Belitung Tahun 2024) - Siska, Siska; Irvani, Ahmad; Nurdin, Muhamad (JYRS: Journal of Youth Research and Studies, 2025)
This study aims to determine the influence of location and knowledge on the interest in saving at Islamic banks among students of IAIN Syaikh Abdurrahman Siddik Bangka Belitung. The variables in this research are location (X₁), knowledge (X₂), and saving interest (Y). The type of research used is quantitative research, employing primary data collected through the distribution of questionnaires to 91 students of IAIN SAS Bangka Belitung. The sampling method applied in this study is probability sampling, resulting in a sample of 91 respondents measured using a Likert scale. Data were analyzed using SPSS Version 26 with the multiple linear regression analysis technique. The findings of this study indicate that: Location has a partial effect on the interest in saving at Islamic banks, with a t-value of 3.917 > t-table value of 1.987 and a significance value of 0.000 < 0.05, thus H₁ is accepted and H₀ is rejected. Knowledge, partially, has no effect on the interest in saving at Islamic banks, with a t-value of 0.905 < t-table value of 1.987 and a significance value of 0.368 > 0.05, thus H₂ is rejected and H₀ is accepted. Location and knowledge, simultaneously, have an effect on the interest in saving at Islamic banks, with an F-value of 33.097 > F-table value of 3.10 and a significance value of 0.000 < 0.05, thus H₀ is rejected and Hₐ is accepted.